The effect of nitrogen fertilizer and row spacing on seed production in setaria sphacelata - Hacker, J.B.; Jones, R.J. (Cali (Colombia), 1971)
Sumario (En)
Ilus.; 18 ref.
Keywords: PRODUCCION DE SEMILLAS; SETARIA SPHACELATA; GRAMINEAS FORRAJERAS; APLICACION DE ABONOS; ABONOS NITROGENADOS; ESPACIAMIENTO